Philosophy of Logic : foundations of philosophy - Quine, W.V (Prentice-Hall of India, 1979)
Philosophy of Logic : foundations of philosophy / Quine, W.V. -- New Delhi: Prentice-Hall of India, 1979 160 Q6 No. of Copies : 1